2023
DOI: 10.1002/qre.3265
|View full text |Cite
|
Sign up to set email alerts
|

Grey wolf optimizer and hybrid PSO‐GWO for reliability optimization and redundancy allocation problem

Abstract: Analysis and optimization of system reliability have very much importance for developing an optimal design for the system while using the available resources. Several studies are centered towards reliability optimization using metaheuristics. In this study, a recently developed metaheuristic optimization algorithm called hybrid PSO-GWO (HPSGWO) to solve the reliability-redundancy optimization problem has been proposed. The HPSGWO fuses the Particle Swarm Optimization's (PSO) exploitation ability with the grey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Experimental results indicated that it was a high-performing algorithm in global optimization. With the same goal, a recently developed metaheuristic optimization algorithm called hybrid PSO-GWO [50] has been proposed to improve exploitation and exploration ability.…”
Section: Related Workmentioning
confidence: 99%
“…Experimental results indicated that it was a high-performing algorithm in global optimization. With the same goal, a recently developed metaheuristic optimization algorithm called hybrid PSO-GWO [50] has been proposed to improve exploitation and exploration ability.…”
Section: Related Workmentioning
confidence: 99%
“…However, considering that the switch is imperfect, that is, switch reliability is less than 1.0, Coit [3] showed that the optimal redundancy strategy should be employed depending on the condition of the redundant design, such as the reliability and redundancy level of the switch and components. Since then, many studies, such as [3][4][5][6][7][8][9][10][11][12][13], have presented the reliability optimization problem of employing either an active or cold standby (hereafter referred to as standby) redundancy strategy for each subsystem. Moreover, the reliability optimization problem has been applied in various real-world industrial fields such as spaceflight [14], manufacturing systems [15], and sliding window systems [16].…”
Section: Introductionmentioning
confidence: 99%
“…And therefore, the performance of the GA-PSO algorithm is enhanced obviously. Bhandari et al [26] develop a new metaheuristic optimization algorithm called hybrid HPSGWO, which effectively combines the exploitation ability of PSO and the exploration ability of GWO (PSO) to search for optimal solutions. The experimental results prove that the proposed HPSGWO algorithm obtains a better numerical result in numerical problems and the reliability-redundancy optimization problem.…”
Section: Introductionmentioning
confidence: 99%